Toxicity and Toxicokinetics of a Four-Week Repeated Gavage of Levamisole in Male Beagle Dogs: A Good Laboratory Practice Study - Jiahui Zhang; Junxiang Wang; Lingfan Chen; Xiangbin Yu; Shuihua Zhang; Yue Yu (MDPI AG, 2024)
Levamisole (LVM) is considered an immunomodulatory agent that has the potential to treat various cancer and inflammation diseases. However, there is still much debate surrounding the toxicokinetic and toxicological information of LVM. Therefore, it is crucial to assess its toxicity to provide useful data for future human LVM risk assessments. In this study, a barrier environment was established under the guidance of good laboratory practice (GLP) at the Fujian Center for New Drug Safety Evaluation. Male beagle dogs were orally administered with 5, 15, and 30 mg/kg of LVM daily for four weeks. Toxicity assessment was based on various factors such as mortality, clinical signs, food and water consumption, body weight, body temperature, electrocardiogram, ophthalmological examination, hematology, serum biochemistry, organ/body coefficients, histopathological study, and toxicokinetic analysis. The results of this study showed that LVM did not exhibit any significant toxicological effects on beagle dogs at the exposure levels tested. A no observed adverse effect level (NOAEL) of LVM was set at 30 mg/kg/day for male beagle dogs, which is equivalent to a 12-fold clinical dose in humans. Moreover, the repeated exposure to LVM for four weeks did not lead to any bioaccumulation. These findings provide valuable insights for future human LVM risk assessments.